The Collection of Incunabula of the National Library of Colombia: Tracks and Silences in its Formation - López Arévalo, Robinson (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article tracks the formation of the inculabula collection that forms part of the stock of the National Library of Colombia, manifesting how this collection has been subject to different forms of organization, systems of cataloguing and places. Factors such as: the reason and moment of entry of books account for the relation that individuals and communities have held with ancient and rare books. In order to do this, we examined different catalogues and indexes that the Library has had, as well as the reports presented by its directors. This study constitutes a first step towards the recognition and dissemination of Colombian bibliographical patrimony.